2017
DOI: 10.1016/j.theriogenology.2016.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Dietary polyunsaturated fatty acid supplementation of young post-pubertal dairy bulls alters the fatty acid composition of seminal plasma and spermatozoa but has no effect on semen volume or sperm quality

Abstract: Dietary polyunsaturated fatty acid supplementation of young postpubertal dairy bulls alters the fatty acid composition of seminal plasma and spermatozoa but has no effect on semen volume or sperm quality, Theriogenology, 90, pp. 289-300. were assessed. On weeks -2, -1, 0, 10, 11, 12, semen was packaged into 0.25 mL 28 straws and frozen using a programmable freezer. On weeks -1, 7 and 11; a sub-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 33 publications
(1 reference statement)
2
18
0
Order By: Relevance
“…In addition, retaining the membrane flexibility of the sperm tail is crucial for the sperm movement. High level of PUFAs in the sperm membrane assures higher fluidity of sperm cells, hence increasing the kinetic traits of the sperm [56][57][58].…”
Section: Relevance Of Fatty Acid Metabolism In Spermatogenesismentioning
confidence: 99%
“…In addition, retaining the membrane flexibility of the sperm tail is crucial for the sperm movement. High level of PUFAs in the sperm membrane assures higher fluidity of sperm cells, hence increasing the kinetic traits of the sperm [56][57][58].…”
Section: Relevance Of Fatty Acid Metabolism In Spermatogenesismentioning
confidence: 99%
“…It appears that DHA-enriched oils or the use of nutraceuticals have systematically improved the quality of fresh semen after several weeks, at least regarding the classical motility parameter [4951]. When the fatty acid composition of sperm was assessed, an increase in n -3 fatty acids was observed after DHA-rich oil supplementation [51, 52], with at least in one of these studies, a parallel increase in n -3 fatty acid plasma concentrations. In frozen-thawed sperm, analyzed from the same bulls, the results were not always consistent, with some studies showing no improvement in sperm quality [49], others showing a positive effect on motility parameters [51], or the percentage of sperm with intact acrosome [52].…”
Section: Lipid Overload and Oxidative Stress: Links Consequencesmentioning
confidence: 99%
“…When the fatty acid composition of sperm was assessed, an increase in n -3 fatty acids was observed after DHA-rich oil supplementation [51, 52], with at least in one of these studies, a parallel increase in n -3 fatty acid plasma concentrations. In frozen-thawed sperm, analyzed from the same bulls, the results were not always consistent, with some studies showing no improvement in sperm quality [49], others showing a positive effect on motility parameters [51], or the percentage of sperm with intact acrosome [52]. A study reported that the lipid composition of sperm improved after the freeze-thaw procedure, with an increase in the proportion of n -3 PUFA in sperm from fish oil-supplemented bulls compared to control animals, in association with improved sperm quality assessed by viability, progressive motility, and morphology [50].…”
Section: Lipid Overload and Oxidative Stress: Links Consequencesmentioning
confidence: 99%
“…Dietary supplementation may also be an alternative, since the greater fragility of senior bull semen in cryopreservation and its susceptibility to oxidative stress may bring a new perspective on the use of PUFAs and/or inclusion of antioxidants in the diet of animals. Several studies have described that incorporation of PUFAs in the diet improves sperm quality in both fresh and frozen semen (Gürler et al, 2015;Selvaratnam et al, 2015;Khoshvaght et al, 2016;Van Tran et al, 2017) and that animals with lowquality semen may be major beneficiaries of this type of supplementation (Byrne et al, 2017).…”
Section: Tablementioning
confidence: 99%